1989
DOI: 10.1016/0741-5214(89)90348-0
|View full text |Cite
|
Sign up to set email alerts
|

Recognition and management of Budd-Chiari syndrome: Report of one hundred cases

Abstract: Budd-Chiari syndrome is an unusual form of portal hypertension caused by occlusion of the hepatic venous outflow, and it is often confused with portal hypertension caused by liver cirrhosis. Its prognosis is poor, and optimal therapy remains to be established. This is a report of 100 confirmed cases of this syndrome treated from December 1982 to March 1988 at two vascular centers in China. Sixty-two male and 38 female patients, 15 to 62 years of age (mean age, 32.6 years) were treated. Seventy-six patients had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(28 citation statements)
references
References 8 publications
0
28
0
Order By: Relevance
“…In our series, IVC involvement in the majority of cases was due to IVC thrombosis. Previously, MOVC and IVC thrombosis were considered to be idiopathic in origin by most Indian and Asian workers [5,6,11,[13][14][15]17,35,49,50,53,54] ; but this view has been challenged recently in a few reports [22,29,30,42,[55][56][57][58] . In cases of IVC thrombosis in our study, the etiology was identified in 50%.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, IVC involvement in the majority of cases was due to IVC thrombosis. Previously, MOVC and IVC thrombosis were considered to be idiopathic in origin by most Indian and Asian workers [5,6,11,[13][14][15]17,35,49,50,53,54] ; but this view has been challenged recently in a few reports [22,29,30,42,[55][56][57][58] . In cases of IVC thrombosis in our study, the etiology was identified in 50%.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] Surgery though successful, carries higher risk of complications in patients who already had impaired liver function. [3][4][5] Mortality in surgical group is higher-33-40% (Kimura et al & Iwaragi et al).…”
Section: Discussionmentioning
confidence: 99%
“…Obstruction of the hepatic portion of the inferior vena cava (IVCO) is a form of BCS commonly seen in Asia [1][2][3][4][5][6][7][8][9] and Africa [10][11][12] but rarely reported from western countries [13,14]. It is a primary disease of the hepatic portion of the IVC caused by bacterial infection.…”
Section: Introductionmentioning
confidence: 99%